2020
DOI: 10.1101/2020.06.26.170761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sustained neural rhythms reveal endogenous oscillations supporting speech perception

Abstract: Rhythmic sensory or electrical stimulation will produce rhythmic brain responses. These rhythmic responses are often interpreted as endogenous neural oscillations aligned to the stimulus rhythm. However, stimulus-aligned brain responses can also be explained as a sequence of evoked responses, which only appear regular due to the rhythmicity of the stimulus, without necessarily involving underlying neural oscillations. To distinguish evoked responses from true oscillatory activity, we tested whether rhythmic st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 90 publications
(168 reference statements)
1
14
1
Order By: Relevance
“…This is consistent with the proposed role for beta oscillations of the motor system for sensory predictions [44], in addition to its likely primary function in timed movement preparation [65,66] and further supported by the rebound peak latency scaling with the period in a rhythmic motor task [65]. In terms of a correlation with behaviour in the sensory domain, as suggested for rhythmic motor learning by [60], or a possible specific role in the processing of speech [67,68], further work is needed.…”
Section: Functional Interpretationssupporting
confidence: 73%
“…This is consistent with the proposed role for beta oscillations of the motor system for sensory predictions [44], in addition to its likely primary function in timed movement preparation [65,66] and further supported by the rebound peak latency scaling with the period in a rhythmic motor task [65]. In terms of a correlation with behaviour in the sensory domain, as suggested for rhythmic motor learning by [60], or a possible specific role in the processing of speech [67,68], further work is needed.…”
Section: Functional Interpretationssupporting
confidence: 73%
“…A first tentative explanation for the present results is that speech-brain tracking would not always reflect linguistic processing in speech. Speech-brain tracking could reflect a domaingeneral temporal attention mechanism (Schroeder & Lakatos, 2009) that would influence speech parsing and hence comprehension (Kösem et al, 2018;2020;van Bree et al, 2021). An alternative explanation is that speech-brain tracking would correctly mark the processing of phrasal and sentential information in speech, and that linguistic processing of unattended speech would be limited to phonological, sub-lexical and /or lexical semantic level.…”
Section: Discussionmentioning
confidence: 99%
“…This phase shift could result in higher intertrial phase coherence several cycles after the stimulus ceases. Indeed, some studies have found shifts in phase on this basis [ 28 30 ]. However, as Fig 1C shows, poststimulus, the oscillator reverts to its intrinsic (spontaneous) frequency.…”
Section: What An Oscillator Is Notmentioning
confidence: 99%